2008
DOI: 10.1038/nature06866
|View full text |Cite
|
Sign up to set email alerts
|

BCR–ABL1 lymphoblastic leukaemia is characterized by the deletion of Ikaros

Abstract: The Philadelphia chromosome, a chromosomal abnormality that encodes BCR-ABL1, is the defining lesion of chronic myelogenous leukaemia (CML) and a subset of acute lymphoblastic leukaemia (ALL). To define oncogenic lesions that cooperate with BCR-ABL1 to induce ALL, we performed a genome-wide analysis of diagnostic leukaemia samples from 304 individuals with ALL, including 43 BCR-ABL1 B-progenitor ALLs and 23 CML cases. IKZF1 (encoding the transcription factor Ikaros) was deleted in 83.7% of BCR-ABL1 ALL, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
948
4
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 968 publications
(1,013 citation statements)
references
References 28 publications
49
948
4
12
Order By: Relevance
“…These factors are characteristic of the hematopoietic system and are specifically expressed at different stages of the lymphoid branch. Recent studies highlight the importance of genetic alterations undergone by Ikaros family members in various hematologic neoplasias (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…These factors are characteristic of the hematopoietic system and are specifically expressed at different stages of the lymphoid branch. Recent studies highlight the importance of genetic alterations undergone by Ikaros family members in various hematologic neoplasias (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…38,39 In the present cohort study, IKZF1-deletions were analyzed in 52.5% of the subjects, which made it difficult to directly compare the impact of the LPC phenotype or IKZF1-deletions on post-HSCT outcomes. It should be noted, however, that our preliminary results demonstrated that the frequency of IKZF1-deletions at diagnosis were comparable between the two phenotypic groups, which emphasizes the prognostic significance of the LPC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with germline mutations that inactivate the transcriptional regulator Ikaros (gene symbol Ikzf1) develop T-ALL exclusively [23,25] and the resulting malignancies often have activating NOTCH1 mutations [6,23,24]. Ikzf1 somatic mutations are also frequently found in combination with NOTCH1 mutations in mouse retrovirus-promoted T-ALL [18] and in human B-ALL and T-ALL [26,27]. Short, dominant negative forms of Ikaros generated by alternative splicing have also been found in human T-ALL [28,29] although this has not been found in other T-ALL series [30].…”
Section: Introductionmentioning
confidence: 99%